Advanced Compressible and Elastic 3D Monoliths beyond Hydrogels. (23rd August 2019) - Hu, Yijie; Chen, Zehong; Zhuo, Hao; Zhong, Linxin; Peng, Xinwen; Sun, Run‐Cang
Abstract: 3D monoliths have undergone great progress in the past decades in scientific and engineering fields. Especially, compressible and elastic 3D monoliths (CEMs) hold great promise in a series of applications, such as pressure/strain sensing, energy storage, oil/water separation, and thermal insulation, attributed to their unique mechanical properties and multifunctionality (e.g., conductivity, thermal stability, and high adsorption capacity). Recently, plenty of advanced CEMs have been developed from 1D and 2D building blocks, polymers, and biomass via various methods. Herein, the latest progress in controllable design and preparation of advanced CEMs, which mainly refer to aerogels, sponges, and foams, are reviewed in terms of their structural units and applications. The relationship between structure and mechanical performances of CEMs is discussed. Moreover, their applications in sensing, energy storage and conversion, water treatment, fire‐resistance, and electromagnetic interface shielding are presented. Finally, the challenges and future opportunities of CEMs are also discussed. Abstract : Recently, plenty of advanced three‐dimensional (3D) compressible and elastic monoliths (CEMs) have been developed. Herein, the latest progress in controllable design and preparation of CEMs beyond hydrogels is summarized. The relationship between structure and mechanical performances of CEMs is discussed, and their applications in sensing, energy storage and conversion, water treatment, fire‐resistance, and electromagnetic interface shielding are presented.